Evaluating Valency-Based Topological Indices of Polyketide Antibiotics through M-Polynomial Analysis - Priyadharsini G; Amudhamalar V; Savitha S; P.Sathish; S.Shilpa Ivin Emimal (Utilitas Mathematica, 2025)
This paper presents an investigation of the structural properties of various short-lived medications utilizing mathematical chemistry methods. The M-polynomial and its complement, are employed to derive and analyze several topological indices and co-indices, such as the first and second Zagreb indices, the F-index, the reformulated Zagreb index, the modified Zagreb index, and the harmonic index. These indices are computed for a set of short-acting medications, including diorcinol, aspilactonol, ascomycotin, aspiketolactonol, aspyronol, engyodontiumone, and lindgomycin. The findings provide valuable insights into the molecular topology and structural characteristics of these pharmaceutical compounds.